Antičnyj ekfrasis na službe idejam modernizma - Kovarskaja, Julija (Slavistična revija, 2016)
According to Fyodor Dostoyevsky, the eternal harmony embodied in literature and art can act on the soul with such a force that it makes our spirit more sensitive to the effect of beauty, which in a particular moment can have a beneficial effect on our emotional state and play a redemptive role in our destiny. The Russian modernist writer, Leonid Andreyev, develops this idea in his Christmas story "The little angel", which is focused on a description of an object of decorative art-a waxen angel. The visual animation of the image of an angel and the supernatural, mysterious, and transforming power hidden in the image is created in the text using an ancient literary device-ekphrastic
Keywords: "Angeloček"; Andreev, Leonid Nikolaevič, 1871-1919; art; beauty; božična zgodba; Christmas story; harmonija; harmony; kratka proza; lepota; Modernism; modernizem; ruska književnost; Russian literature; short story; Silver Age; umetnost